Changes in Alcohol Habits Among Workers During the Confinement of COVID-19: Results of a Canadian Cross-Sectional Survey. (July 2021) - Mongeau-Pérusse, Violaine; Rizkallah, Elie; Bruneau, Julie; Chênevert, Denis; Menvielle, Loick; Jutras-Aswad, Didier
Background: The restrictions implemented around the world to contain the spread of the coronavirus disease 2019 (COVID-19) impact workers. Emotional distress and maladaptive behaviors such as alcohol misuse are expected, particularly in vulnerable groups such as front-line health workers. In the present study, we examined if alcohol consumption behaviors in Quebec workers changed during confinement of the COVID-19 pandemic, and whether healthcare workers reported specific patterns of changes. Methods: Data were obtained from an anonymous online survey conducted among adult workers aged ⩾18 years in the province of Quebec, Canada, between May 25, 2020 and June 26, 2020. Participants provided self-reported data regarding sociodemographic including field of work, as well as mental health disorders, alcohol use, alcohol craving, and type of alcohol consumed. Changes in alcohol behaviors were assessed using Wilcoxon signed rank test for categorial variables and paired- t tests for continuous variables. Results: The survey was completed by 847 participants (77.8% women), with 42.5% healthcare workers. Participants reported increased daily alcohol use ( Z = −10.60; P < .001, r = −.372) and alcohol craving ( P < .001, d = 0.485) during the confinement. Only the type of alcohol consumed during the confinement differed between health care workers and other workers (OR = 0.45, P = .003). Health care workers used less high alcohol products during the confinement. Conclusion: Our results show a significant increase in daily alcohol consumption and in alcohol craving during the confinement in the Quebec working population.